2011
DOI: 10.1093/ecam/nep228
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Evaluation of Antrodia camphorata Alcohol Extracts in the Treatment of Non‐Small Cell Lung Cancer Using Non‐Invasive Molecular Imaging

Abstract: This study was carried out to provide a platform for the pre-clinical evaluation of anti-cancer properties of a unique CAM (complementary and alternative medicine) agent, Antrodia camphorata alcohol extract (ACAE), in a mouse model with the advantageous non-invasive in vivo bioluminescence molecular imaging technology. In vitro analyses on the proliferation, migration/invasion, cell cycle and apoptosis were performed on ACAE-treated non-small cell lung cancer cells, H441GL and control CGL1 cells. In vivo, immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Recent experiments showed the importance of p38 in UC, where the use of p38 and ERK inhibitors abrogated colitis [30, 31]. Moreover, a recent study demonstrated that it can be effective for treating human IBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments showed the importance of p38 in UC, where the use of p38 and ERK inhibitors abrogated colitis [30, 31]. Moreover, a recent study demonstrated that it can be effective for treating human IBD.…”
Section: Discussionmentioning
confidence: 99%
“…p38 is known to regulate several target genes that ultimately control infiltration of monocytic cells, acute intestinal inflammation, intestinal electrolyte and water secretion, and cytokine production. Furthermore, it upregulates COX-2 expression in intestinal epithelial cells [30]. Growing evidence indicated that the inhibition of NF- κ B activity (e.g., a direct blockade of RelA (p65), suppression of I κ B α degradation, or IKK β activity) may alleviate the severity of intestinal inflammation [5].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were intraperitoneally administered 300 μL of PBS containing 10 mg/mL of beetle luciferin (Promega, Madison, WI, USA) before they received isoflurane-mediated anesthesia. The quantitative bioluminescence intensity (qBI) was determined as the total photon flux per second [ 26 ]. At the end of the experiment, the mice were euthanized, and the tumors were excised and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have illustrated that AC exhibits a broad spectrum of antitumor activities, including apoptotic, antioxidative, and anti-inflammatory effects on human hepatocellular carcinomas and leukocytes (12)(13)(14)(15). In addition, AC has been reported to induce apoptosis via death receptor-mediated and mitochondrial apoptotic signaling pathways, in hepatocellular carcinoma cells (16,17).…”
Section: Introductionmentioning
confidence: 99%